CPC-066 Identification of Patient Groups with Insufficient Knowledge About Their Medicines at Hospital Discharge. (12th March 2013) - Glisic, V; Jevtic, G; Hrgic, S; Vucetic, V; Popovic, B; Vezmar Kovacevic, S; Culafic, M
Abstract : Background: Hospital patients in Serbia receive information about their medicines from physicians and nurses. Pharmacists are not involved in medicines counselling. In countries with developed health care, pharmacists provide counselling to patients at discharge. Purpose: To establish which groups of hospital patients got the least information about their medicines, since these patients could profit from additional counselling at discharge, provided by pharmacists. Materials and Methods: The study was carried out in five hospitals in Serbia, over a period of 8 weeks. Pharmacists collected clinical data from the patient's medical notes. Patients' knowledge of medicines was assessed through an interview using a structured questionnaire, on the morning of discharge. We evaluated 3 groups of patients according to age, length of hospital stay and number of newly-introduced medicines. They were asked seven questions: if they were informed about all medicines, reasons for treatment, the effects of the drug, duration of treatment, posology and method of administration, undesirable effects and interactions. 'Yes' was awarded two points, 'partially' one and 'no' no points. A total ≤10 of all answers per patient was defined as insufficient knowledge. Results: 148 patients (mean age 60 years) were interviewed. 74% of patients younger than 65 years and 89% of elder patients showed insufficient knowledge. Length of hospital stay had impact on patient knowledge. 70% who stayed more than 20 days had insufficient knowledge vs. 85% who were hospitalised less than 10 days. Insufficient knowledge increased with number of newly-introduced medicines (80% who had 1 vs. 96% who had ≥5 new drugs on discharge). Conclusions: The findings of this study indicate that older patients, those who stay less time in hospital and those who receive more new drugs on discharge need to get more counselling about their treatment. Serbian pharmacists can take a proactive role for these patients. No conflict of interest.